Rekonstruksi Prinsip-Prinsip Perencanaan Pendidikan Islam: Integrasi Nilai Spiritual, Filosofis, dan Profesionalisme dalam Manajemen Modern - Niza, Yesita Rosa; Salmon, Salmon; Asmendri, Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Islamic educational planning is a strategic process that determines the direction, policy, and implementation of educational systems grounded in the values of the Qur’an and Sunnah. This article aims to explore in depth the principles of Islamic educational planning and their relevance to the challenges of modernity and globalization. This study employs a library research method by analyzing various classical and contemporary scholarly sources discussing theories and practices of educational planning from an Islamic perspective. The findings indicate that Islamic educational planning is based on several core principles: comprehensiveness, systematicity, participation, relevance, flexibility, justice, efficiency, accountability, and spirituality. These principles assert that Islamic education aims not only at achieving academic or material outcomes but also at developing students’ character and morality. Integrating spiritual values and professionalism is essential for ensuring quality and competitiveness in Islamic education. This paradigm allows Islamic education to remain adaptive to the dynamics of modern society while preserving its transcendental foundations.